The Mayo Clinic diet - Hensrud, Donald D. (Mayo Clinic, 2017)
Offers a weight loss and lifestyle program that focuses on making smart, healthy choices to reach a healthy weight and stay there, including meal planners, recipes, and psychological tips for ensuring success.